Community Health Needs Assessment in Urban Communities in Kigali City In Rwanda: A Cluster-Randomized Trial - Placide, MUTABAZI; Jean Pierre, NIYITEGEKA; Fidele, NIZEYIMANA (Journal of Public Health International, 2021)
Introduction Reporting of suspected or confirmed communicable diseases is paramount. Although physicians have primary responsibility for reporting, school nurses, laboratory directors, infection control practitioners, daycare center directors, health care facilities, state institutions and any other individuals providing health care services are also required to report communicable disease. Therefore, community health needs assessment in urban communities remains an essential instrument for the rapid and accurate dissemination of epidemiological information on cases and outbreaks of diseases under the national health regulations and other communicable diseases of public health importance, including emerging or re-emerging infections. Purpose of the Study Todescribe relevant medical needs of townspeople so that treatment plans can be developed accordingly. Methods The Study was a cross-sectional with qualitative approach. In-depth interviews and focus group interviews was used as research technique. Data was categorized to look for emerging themes then further distilled to identify any abstract themes that could be understood holistically. Results Urban decision-makers need to advocate the problem of human resources in public health facilities and the mutual health insurance to revise its insurance policy to allow their clients to be received even in private clinics. Dental services was wished to be available in public health centers. Study participants suggested that new useful information could be posted in private public premises rather than to be in public institutions only. Conclusion The patient waiting time, dental services in health centers, and the way of dissemination new health information, mutual health insurance and insufficient human resources are the major concerns of townspeople that they wish improvement.
Keywords: Assessment; community; health; metropolitan; needs; urban